The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/00031348221111517
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Factors Predicting Lymph Node Metastasis Between pT1 Rectal Cancer and pT1 Colon Cancer: A Retrospective Study

Abstract: Background Studies have demonstrated conflicting results regarding factors that predict lymph node metastasis (LNM) in pT1 colorectal cancers. We hypothesized that these discrepancies could be related to different factors predicting LNM between rectal and colon cancer. This study aimed to compare predicting factors for LNM between pT1 rectal and colon cancer. Methods This retrospective study evaluated a prospectively maintained database that included 380 patients with pT1 colorectal cancer from January 2010 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…However, CD31 staining for VI did not have sufficient data for evaluation because it was often assessed in conjunction with elastic staining, 37,76,83 and only a few studies evaluated CD31 staining alone for VI. 38,42 In a previous study, CD31 staining was found to be less likely to detect VI than elastic staining and was not associated with prognosis. 103 Further studies are needed to elucidate the optimal choice of staining methods and their appropriate utilization.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…However, CD31 staining for VI did not have sufficient data for evaluation because it was often assessed in conjunction with elastic staining, 37,76,83 and only a few studies evaluated CD31 staining alone for VI. 38,42 In a previous study, CD31 staining was found to be less likely to detect VI than elastic staining and was not associated with prognosis. 103 Further studies are needed to elucidate the optimal choice of staining methods and their appropriate utilization.…”
Section: Discussionmentioning
confidence: 82%
“…We identified 3451 records from various databases until December 10, 2022. After screening for duplicates, we included 64 studies with 18,097 patients, 17,18,22,36–96 of them, 59 studies evaluated the diagnostic accuracies of HE and additional staining for LVI in LNM in patients with T1 CRC, four reported the interobserver agreement among pathologists for positive LVI, and one reported both outcomes, with eight studies comprising 4062 patients in multivariable analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation